HUBUNGAN POSISI MENGEJAN TELENTANG DAN KOMBINASI DENGAN LAMA KALA II - Nor Asiyah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The uncomfortable straining position of the patients is able to result on the backache that disturb mother during pushing. In fact, supine position is the most preferred position choosen by the rescuers on the other hand that position make no comfort for the patients. Moreover, the second stage labor duration becomes one of the effects of that position in the term of straining. The purpose of this study is to relation the difference between supine position and combination (lateral and semi-setting) toward second stage labor duration. This study was a cross-sectional study. The population was all give birth mothers at the maternity hospital of Fatimah and the midwives in Kasmasita having inclusion and exclusion criteria. The total respondents of this study were 40. The data collected were then tested by using normality test and Mann-Whitney test. The result of this study showed that comparative of second stage labor duration on supine position was longer with the average value of 19.5 standart deviation of 10.9 median of 16 with 3 minutes of the shortest and 40 minutes of the longest. Furthermore, the combination position had the average value of 14.8 standart deviation of 9.7 median of 11 with 5 minutes of the shortest and 45 minutes of the longest (p = 0.036).I n short, second stage labor duration on supine position was longer than combination (Lateral and semi-setting)Keywords: Duration of the second stage of labor, supine position, combination position.